“Listen My Children and You Shall Hear”: Auditory Preferences in Toddlers With Autism Spectrum Disorders. - Paul, Rhea; Chawarska, Katarzyna; Fowler, Carol; Cicchetti, Domenic; Volkmar, Fred (Journal of Speech, Language & Hearing Research, 2007)
Purpose: This study tests the hypothesis that toddlers with autism spectrum disorders (ASD) will show differences from contrast groups in preferences for attending to speech. Method: This study examined auditory preferences in toddlers with ASD and matched groups of (a) typical age-mates, (b) age-mates with nonautistic developmental disabilities, and (c) younger children matched for language age. The experimental procedure measured time spent oriented to auditory stimuli that were created to exemplify language patterns that had been studied in typically developing infants. Results: Findings suggest that toddlers with ASD show a reduced preference for child-directed speech, compared with typical age-mates, but few differences from children with nonautistic developmental disorders. Correlational analysis revealed that time spent listening to child-directed speech by children with ASD was related to their concurrent receptive language ability as well as to receptive language abilities 1 year later. This relationship did not hold for the other groups. Conclusion: The present study supports the hypothesis that children with ASD perform differently from typical peers in auditory preference paradigms and that performance in these tasks is related to concurrent and later language development. Reprinted by permission of the publisher.